(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This study investigates the impact of combat sambo training on the functional readiness of law enforcement cadets. Thirty cadets participated in a 12-week structured combat sambo program designed to improve physical fitness, tactical skills, and operational performance. Results indicate significant improvements in endurance, strength, agility, speed, tactical decision-making, and stress resilience in the experimental group compared to controls. These findings highlight combat sambo as an effective tool for preparing cadets for real-world operational challenges.